Sugar overconsumption during adolescence selectively alters motivation and reward function in adult rats. - Leandro F Vendruscolo (Public Library of Science (PLoS), 2010)
Background There has been a dramatic escalation in sugar intake in the last few decades, most strikingly observed in the adolescent population. Sugar overconsumption has been associated with several adverse health consequences, including obesity and diabetes. Very little is known, however, about the impact of sugar overconsumption on mental health in general, and on reward-related behavioral disorders in particular. This study examined in rats the effects of unlimited access to sucrose during adolescence on the motivation for natural and pharmacological rewards in adulthood. Methodology/principal findings Adolescent rats had free access to 5% sucrose or water from postnatal day 30 to 46. The control group had access to water only. In adulthood, rats were tested for self-administration of saccharin (sweet), maltodextrin (non-sweet), and cocaine (a potent drug of abuse) using fixed- and progressive-ratio schedules, and a concentration-response curve for each substance. Adult rats, exposed or not exposed to sucrose, were tested for saccharin self-administration later in life to verify the specificity of adolescence for the sugar effects. Sugar overconsumption during adolescence, but not during adulthood, reduced the subsequent motivation for saccharin and maltodextrin, but not cocaine. This selective decrease in motivation is more likely due to changes in brain reward processing than changes in gustatory perception. Conclusions/significance Sugar overconsumption induces a developmental stage-specific chronic depression in reward processing that may contribute to an increase in the vulnerability to reward-related psychiatric disorders.